Association of matrilin-3 polymorphisms with spinal disc degeneration and osteoarthritis of the first carpometacarpal joint of the hand. Issue 8 (5th January 2006) - Min, J L; Meulenbelt, I; Riyazi, N; Kloppenburg, M; Houwing-Duistermaat, J J; Seymour, A B; van Duijn, C M; Slagboom, P E
Abstract : Background: Seven polymorphisms in the matrilin-3 (MATN3) gene were previously tested for genetic association with hand osteoarthritis in an Icelandic cohort. One of the variants, involving a conserved amino acid substitution (T303M; SNP5), was related to idiopathic hand osteoarthritis. Objectives: To investigate SNP5 and two other promising polymorphisms (rs2242190; SNP3, rs8176070; SNP6) for association with radiographic and symptomatic hand osteoarthritis phenotypes, as well as other heritable phenotypes. Methods: Polymorphisms were examined in two distinct cohorts of subjects: a population based sample from the Rotterdam study (n = 809), and affected siblings from the genetics, osteoarthrosis and progression (GARP) study (n = 382). Results: The originally described association of T303M with the hand osteoarthritis phenotype was not observed in the populations studied. In the Rotterdam sample, however, carrying the T allele of T303M conferred an odds ratio of 2.9 (95% confidence interval (CI), 1.2 to 7.3; p = 0.02) for spinal disc degeneration. In the GARP study, carriers of the A allele of SNP6 had an odds ratio of 2.0 (95% CI, 1.3 to 3.1, p = 0.004) for osteoarthritis of the first carpometacarpal joint (CMC1) as compared with the Rotterdam sample as a control group. Subsequent haplotype analysis showed that a common haplotype, containing the risk allele of SNP6, conferred a significant risk in sibling pairs with CMC1 osteoarthritis (odds ratio = 1.7 (95% CI, 1.1 to 2.7, p = 0.02)). Conclusions: These associations suggest that the MATN3 region also determines susceptibility to spinal disc degeneration and CMC1 osteoarthritis.